HKS Misinfo Review 2023
DOI: 10.37016/mr-2020-113
|View full text |Cite
|
Sign up to set email alerts
|

Examining accuracy-prompt efficacy in combination with using colored borders to differentiate news and social content online

Abstract: Recent evidence suggests that prompting users to consider the accuracy of online posts increases the quality of news they share on social media. Here we examine how accuracy prompts affect user behavior in a more realistic context, and whether their effect can be enhanced by using colored borders to differentiate news from social content. Our results show that accuracy prompts increase news-sharing quality without affecting sharing of social (non-news) posts or “liking” behavior. We also find that adding color… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Though exploratory analyses revealed that the difference in the nudge effect on sharing and liking was, in itself, nonsignificant (note, however, that the current study was likely underpowered to test for such a difference). These findings suggests that nudge interventions primarily influence sharing behavior, a pattern generally consistent with both past research (e.g., 30 , 43 ) and the desired intent of the intervention. Specifically, nudge-based interventions are designed to reduce the overall propagation of misinformation, rather than any form of positive engagement.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Though exploratory analyses revealed that the difference in the nudge effect on sharing and liking was, in itself, nonsignificant (note, however, that the current study was likely underpowered to test for such a difference). These findings suggests that nudge interventions primarily influence sharing behavior, a pattern generally consistent with both past research (e.g., 30 , 43 ) and the desired intent of the intervention. Specifically, nudge-based interventions are designed to reduce the overall propagation of misinformation, rather than any form of positive engagement.…”
Section: Discussionsupporting
confidence: 86%
“…Social posts used in the 12.5% misinformation condition were generated by the authors and paired with a relevant royalty-free image. Posts were designed to be non-controversial and mimic typical user-generated content people may encounter on social media (e.g., buy and sell, holiday posts, similar to 30 ); however, social posts were not pilot tested.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This could, for example, be achieved in part by nudging users to consider the concept of accuracy while scrolling through their newsfeed (21,24,26) or redesigning how social cues are displayed (20). A related concern is the context collapse of social media (27) whereby many audiences and types of content are flattened into a single context, which could be mitigated by organizing content and audiences thematically to delineate spaces where accuracy is (e.g., news) versus is not (e.g., family photos) central (28). Alternatively, platforms could emphasize the building of connections between content rather than directly sharing content with an audience.…”
Section: Discussionmentioning
confidence: 99%
“…A series of lab and field experiments have reported that shifting attention to accuracy (e.g., by asking about the accuracy of an unrelated news headline) improved the quality of people's news-sharing decisions (Pennycook, Epstein, et al, 2021;Pennycook, McPhetres, et al, 2020). Similar findings have been replicated in numerous studies (Arechar et al, 2023;Bhardwaj et al, 2023;Calianos et al, 2022;Capraro & Celadin, 2023;Ceylan et al, 2023;Epstein et al, 2023;Offer-Westort et al, 2022;Organisation for Economic Co-operation and Development, 2022;Rasmussen et al, 2022), although some others have found mixed or nonsignificant results (Gavin et al, 2022;Pretus et al, 2022;Roozenbeek et al, 2021).…”
Section: Research Articlementioning
confidence: 69%